PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP LOYALITAS KARYAWAN - Mahayuni, Anak Agung Putri; Dewi, A.A. Sagung Kartika (E-Jurnal Manajemen; Vol 9 No 5 (2020), 2020)
The purpose of this study is to explain and analyze the effect of transformational leadership, work environment and motivation on employee loyalty partially and simultaneously. The purpose of this study is to explain the effect of transformational leadership, work environment and motivation on employee loyalty. The population of this study is all employees at PT. Mardika Griya Prasta, amounting to 105 people and not including company leaders, because it talks about leadership so that leaders are not included in the population. Based on calculations with the Slovin formula the number of samples obtained by 51 respondents. The method of determining the sample in this study was done by proportionate random sampling. The analysis technique used in this study is multiple linear regression test. The results showed that transformational leadership, work environment and motivation had a positive and significant effect on employee loyalty. The results of this  study imply that if transformational leadership is applied the better the higher the level of employee loyalty, a good work environment can increase employee loyalty, and the higher the motivation of employees at work, the higher the employee loyalty will be. Keywords : transformational leadership, work environment, motivation, employee loyalty